Hermeneutics and Hindu Thought: Toward a Fusion of Horizons
XII, 250 p.
Keywords: The emergence of Hinduism as a field of study in the Western academia coincides with the development of modern hermeneutics. Despite this coemergence, and the rich possibilities inherent in a dialectical encounter between the theories of modern and pre-modern hermeneutics and those of Hindu hermeneutical traditions, this potential has not been tapped within the boundaries of religious studies. This volume sets out to initiate such an interface. Some essays in this volume, such as those by Shrinivas Tilak, Sharada Sugirtharajah, and Purushottama Bilimoria examine the impact of Western hermeneutics on the Indian religious landscape. Others, just as those by Jeffrey Long, Klaus Klostermaier, Aditya Adarkar and Leena Taneja, offer insights into traditional Hindu philosophical principles and into concepts pertaining to cross-cultural hermeneutical frameworks. Still others, such as those by Stephen Phillips and T.S. Rukmani, are concerned with the application of a philosophical approach to hermeneutical engagement with Hindu texts, in order to arrive at a more comprehensive interpretation. An introduction by Rita Sherma and a conclusion by Arvind Sharma book-end the volume.